The vicar of Dibley. Series 1 [videorecording (DVD)] - Humphreys, Dewi; French, Dawn; Waldhorn, Gary, 1943-; Fleet, James (BBC Video ; Distributed by Warner Home Video, 2003)
Presents the complete first season of the BBC's popular television series "The Vicar of Dibley" in which a female vicar with a sharp wit and a laid-back attitude brings new ideas to a rural British community.